2020
DOI: 10.1186/s13223-020-00428-y
|View full text |Cite
|
Sign up to set email alerts
|

Local eosinophils are associated with increased IgA subclass levels in the sinonasal mucosa of chronic rhinosinusitis with polyp patients

Abstract: Background: Chronic rhinosinusitis (CRS) describes an inflammatory condition affecting the sinonasal mucosa. As the immune system players such as immunoglobulins play prominent roles in the development of CRS, we aimed to investigate the expression of IgA subclasses and factors involved in IgA class switching in the sinonasal mucosa of CRS patients. Methods: Specimens were collected from the sinonasal mucosa of the healthy controls and CRS patients. Histological assessments were performed by H&E and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, at the level of local IgA production, differences are detected between CRS patients and healthy controls. Four studies found higher levels of IgA (total and/or IgA1) in sinus tissue from patients with CRSwNP ( 15 , 109 , 113 , 115 ) and three of them showed increased numbers of IgA+ plasma cells ( 109 , 113 , 115 ). Two studies reported also on an overexpression of BAFF, an important inducer of local IgA class switching, in CRSwNP patients ( 112 , 115 ).…”
Section: Role Of Iga In Upper Airway Diseasementioning
confidence: 98%
“…However, at the level of local IgA production, differences are detected between CRS patients and healthy controls. Four studies found higher levels of IgA (total and/or IgA1) in sinus tissue from patients with CRSwNP ( 15 , 109 , 113 , 115 ) and three of them showed increased numbers of IgA+ plasma cells ( 109 , 113 , 115 ). Two studies reported also on an overexpression of BAFF, an important inducer of local IgA class switching, in CRSwNP patients ( 112 , 115 ).…”
Section: Role Of Iga In Upper Airway Diseasementioning
confidence: 98%